The World Bank Group and the Environment 1996 : Environment Matters at the World Bank - World Bank (The World Bank, 1997)
This publication contains the annual review for fiscal 1996 (July 1995-June 1996) and a 10-year accounting of the project portfolio in a project matrix (Appendix). The annual review portion of the publication is divided into four sections:an overview, a series of regional review, a set of reviews on a spectrum of environmental and social issues, and a brief scan of relevant publications. The environmental and social issues discussed include:biodiversity conservation; fostering global warming solutions through energy efficiency, demand side management and renewable technologies; linking physical environmental effects to economic impacts; legal aspects of environmental management; building strategic alliance to avoid duplicating efforts in environmental work; Bank's work on pollution management and technology policy; engaging private sector into environmental investments; enhancing participatory approaches in decisionmaking; and freshwater, coastal and marine resource management. In addition, a new column called Reflection sets the context for the Bank's work in the larger global agenda drawn up in Rio's Agenda 21 in 1992